AI on The Job Guide to Successful Human-Machine Collaboration - Moring, Andreas (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
This book is a practical guide to using artificial intelligence with motivated employees in companies and organizations. You will learn what the prerequisites are for people to look forward to productive collaboration with "intelligent machines". Because this is the only way to leverage the full potential of AI. This book is a translation of the original German 1st edition KI im Job by Andreas Moring, published by Springer-Verlag GmbH Germany, part of Springer Nature in 2021. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. To this end, you will receive an overview of how and where AI can be used in companies and how to identify the right areas of application for AI in your company. The main issue here is the following: which tasks will be taken over by AI in the future and which should continue to be performed by employees. These decisions change processes and tasks and require practical change management and motivation. In this book, you will learn how to motivate and inspire people for these new tasks, so that the steps towards using AI in the work environment can succeed in the best possible way. About the Author: Prof. Dr. Andreas Moring is Professor of Digital Business, Innovation & AI at the International School of Management. He is founder and director of the JuS.TECH Institute for AI and Sustainability, co-founder of the WeGoFive initiative for productive human-AI cooperation and topic sponsor for human-AI cooperation at the Artificial Intelligence Center ARIC in Hamburg. .
Preface -- 1. introduction -- 2. man and machine -- 3. artificial intelligence -- 4. theories of technical adaptation -- 5. basic principles of motivation -- 6. self determination theory -- 7. jobs demands resources -- 8. artificial intelligence and employee motivation -- 9. employees' expectations towards "AI jobs" -- 10. guide for practical AI implementation.
Keywords: Psychology, Industrial; Personnel management; Economics; Leadership; Work and Organizational Psychology; Human Resource Management; Organizational Psychology; Economics; Leadership Psychology; Human Resource Development